An investigation into the nature of mathematics connections used by selected Grade 11 teachers when teaching algebra : a case study - Kanyanda, Ester Ndahekomwenyo (Rhodes University, Faculty of Education, Department of Education, 2015)
The purpose of this study was to investigate the nature of mathematical connections used by selected teachers when teaching the topic of algebra and to investigate their perceptions of their use of connections. The participants were selected on the basis of teaching experience as well as their willingness to share their ideas. An interpretive paradigm was used to collect and analyse data. The data was collected from three participating teachers. These participants were selected from the three secondary schools in the town of Tsumeb in Namibia. I used video recordings of two lessons per teacher as well as semi-structured interviews as my tools to gather data. After the two lessons were video recorded, I conducted a workshop with the teachers to introduce them to the 5 types of mathematical connections pertinent to this study. We analysed the videos together using Businskas' framework as a basis for analysis. This then formed part of the stimulated recall interviews. It was found that, even though teachers were not aware of the concept of mathematical connections before our interactions, there was strong evidence of connections being made and used in their lessons. The two types of connections that were used most frequently (24.1 percent each) were procedural and instruction-oriented connections respectively. Part-whole relationships connections were used the least with a frequency of 12 percent. All three teachers agreed that they needed to make more connections when teaching and that they would think more about connections in future, particularly when preparing their lessons. The study makes recommendations to encourage the continuous use of connections in teaching mathematics.
Keywords: Mathematics -- Study and teaching (Secondary) -- Namibia -- Tsumeb; Algebra -- Study and teaching (Secondary) -- Namibia -- Tsumeb; Connections (Mathematics); Teacher effectiveness -- Namibia -- Tsumeb